The Development of Critical Thinking Skills and Emotional Intelligence Test Instruments with Problem-Based Learning (PBL) Learning Model: A Study on Educational Administration Students - Sakalessy, Alexander; Ratumanan, Tanwey Gerson (Publikasi Pendidikan, 2024)
One of the essential components for students to live in the future is to have life skills. Life skills, namely critical thinking and emotional intelligence, are critical for students. One of the learning models that can facilitate this is problem-based learning (PBL), which is an innovative model. Therefore, this research aims to develop PBL-based test instruments to improve students' critical thinking skills and emotional intelligence. The development model used in this research is ADDIE. The validation results show that the instrument expert test obtained 95.5%, 85.5% for scientific content, 83.5% for learning model experts, 92% for individual trials, and 95.5% for small group trials. Based on the results of the analysis of the research on the development of critical thinking skills instruments and emotional intelligence with the PBL model, it can be concluded that the instrument developed with excellent qualifications and is suitable for use because it has passed a series of stages of instrument development and has fulfilled the validity elements of the experts and has been tested on students. Therefore, future suggestions are that trials can be carried out on a larger scale and develop critical thinking skills instruments and emotional intelligence with the PBL model can be further developed using different materials.